Dari Mudharabah ke Investasi Syariah: “Evolusi Pemikiran Ekonomi Islam dalam Perspektif Ibnu Khaldun dan Muhammad Yunus”. - Hermansyah, Bayu; Reza, Muhammad Faizal; Komariah, Rizka (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2024)
This study aims to analyze and compare the concepts developed by Ibn Khaldun and Muhammad Yunus in the context of Islamic economics and microfinance. The main focus of this research is on the concept of mudarabah proposed by Ibn Khaldun in his Muqaddimah and the microfinance model introduced by Yunus through Grameen Bank. This research employs a qualitative method with a library research approach, analyzing literature related to the thoughts of both figures and their application in the Islamic finance system and modern microfinance. The results of the study show that although these two concepts originated in different contexts, they share similarities in the principles of social justice and fair risk-sharing between the parties involved in economic transactions. Mudarabah, as a partnership model emphasizing fairness in profit and loss distribution, aligns with the basic principles of Yunus’s microfinance model, which provides opportunities for the poor to access capital without interest. The application of both concepts in the modern Islamic finance system, particularly in the Islamic investment and microfinance sectors, can contribute to the creation of a more inclusive and sustainable financial system. This study offers new insights into the relevance of Ibn Khaldun’s and Yunus's economic thoughts in addressing contemporary socio-economic challenges.